PENGEMBANGAN MODUL PRAKTIKUM BIOLOGI YANG MEMANFAATKAN BAHAN ALAM SEBAGAI SUMBER BELAJAR BAGI SISWA DI SEKOLAH MENENGAH ATAS (SMA) - Mariana Rengkuan Rengkuan; Dian H O Howan (LPPM UNIMA, 2016)
The aim of this research is to generate biology laboratory work module which utilize natural products as learning resource for students in senior high school. This module developed using Borg and Gall model which has been adapted with the needs and aims of this research, therefore, it gained four major stages that will be passed. These stages namely: needs analysys and literature study, matter development (based on needs), expert validation and field test (experimental class). On expert validation limited to matter expert validator whilst for field test, it was decided on students from XII science class as experimental class. The result of this research shown that laboratory module that utilized natural products can be used as learning resource for students in senior high school.